Conserved TCR beta chain usage in reactive arthritis; evidence for selection by a putative HLA-B27-associated autoantigen. - May, E; Dulphy, N; Frauendorf, E; Duchmann, R; Bowness, P; Lopez de Castro, J; Toubert, A; Märker-Hermann, E (2002)
Previous work suggested that expanded CD8+ T-cell clones in the synovial fluid (SF) of HLA-B27+ patients with reactive arthritis (ReA) preferentially use the T-cell receptor variable region (TCRBV) 1, similar CDR3 sequences, and joining region (BJ) 2S3. To determine the range of conservation and disease-specificity of CDR3-sequences, we analyzed the TCRBV1-J2S3 repertoire from 33 healthy HLA-B27+ individuals, patients with various types of spondyloarthropathies (SpA), and with rheumatoid arthritis (RA) by CDR3-spectratyping. After collection and database submission of all available TCRB-CDR3 from HLA-B27-restricted or SpA-derived T cells, we systematically screened the entire human sequence database for sequences similar to the B27/SpA-related CDR3. Spectratyping revealed expanded T cell clones using conserved TCRBV1J2S3 in the SF from 5/6 of the patients with acute ReA but not among the controls. In database searches, 50 HLA-B27 or SpA-related CDR3-sequences generated similar clusters of matched sequences, and matched reciprocally. Identical or closely related sequences were identified in 15 different individuals and a canonical ReA-associated TCRB was defined [BV1-CASSVG(V/I/L)(Y/F)STDTQYF-J2S3]. All but one patient-derived conserved sequences originated from acute stage ReA-patients, and were not present among approximately 3800 other human TCRB sequences in the database. Five of the conserved sequences originated from T cell clones that recognized uninfected cells in an HLA-B27-restricted fashion, implying a role of HLA-B27-restricted CD8+ T cells specific for a ubiquitous self- or cross-reactive microbial determinant in the early phase of ReA. Related sequences were independently identified in four different laboratories. The consensus TCRB motif could be a helpful diagnostic marker in HLA-B27-associated 'undifferentiated arthritis'.